2017
DOI: 10.2147/ijn.s140096
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic apoptotic effects of apigenin TPGS liposomes and tyroservatide: implications for effective treatment of lung cancer

Abstract: To develop an alternative treatment for lung cancer, a combination of two potent chemotherapeutic agents – liposomal apigenin and tyroservatide – was developed. The therapeutic potential of this combination was investigated using A549 cells. Apigenin and tocopherol derivative-containing D-alpha-tocopheryl polyethylene glycol 1000 succinate (TPGS) liposomes might improve the delivery of apigenin to tumor cells, both in vitro and in vivo. Importantly, compared to either agent alone, the combination of apigenin T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Apigenin has gained increasing attention due to its anti-inflammatory, antioxidant, sedative, antihypertensive and antitumor effects [5, 6]. Apigenin has also been shown to suppress cell survival of a wide variety of tumor cells, including prostate cancer, breast cancer, melanoma and leukemia cells [710]. Several mechanisms for its antitumor effect have been elucidated, including cell cycle arrest with dysregulation of cell cycle proteins, induction of apoptosis, inhibition of fatty acid synthesis, production of reactive oxygen species, and inactivation of survival signaling [11].…”
Section: Introductionmentioning
confidence: 99%
“…Apigenin has gained increasing attention due to its anti-inflammatory, antioxidant, sedative, antihypertensive and antitumor effects [5, 6]. Apigenin has also been shown to suppress cell survival of a wide variety of tumor cells, including prostate cancer, breast cancer, melanoma and leukemia cells [710]. Several mechanisms for its antitumor effect have been elucidated, including cell cycle arrest with dysregulation of cell cycle proteins, induction of apoptosis, inhibition of fatty acid synthesis, production of reactive oxygen species, and inactivation of survival signaling [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to colorectal cancer, apigenin/tyroservatide-loaded liposomes were applied for lung cancer therapy. It was shown that these delivery systems are able to remarkably stimulate apoptosis and cell cycle arrest at the G2 phase in A549 cells (Figure 6) (Jin et al, 2017). This is due to providing targeted delivery and enhancing the accumulation of apigenin in cancer cells.…”
Section: Apigenin-loaded Nanovehiclesmentioning
confidence: 95%
“…Cytotoxicity data were analyzed to determine the 50% inhibitory concentration (IC 50 ) . Synergistic effects were evaluated using CompuSyn and Chou-Talalay's plot, as described previously [28].…”
Section: Cell Viability Assaymentioning
confidence: 99%